PERCEPTIONS OF PLAYERS OF COMPETITION OF HANDBALL AMONG HIGH SCHOOL IN PERSPECTIVE OF SPORT SCHOOL (Fiep Bulletin - online, 2014)
The study analyses the opinions of participants in Handball interstudents competitions from different schools, with the aim to analyse the development in this sport.  The competitions held at this level are, in the majority, sponsored by private institutions.  There were twenty-five male and female students of four schools of high school from different areas of Rio de Janeiro during the year 2006. There were collected statements and were analysed from semi-structural interview as recommended by Bardin's (1994) through contents analysis.The results of interstudents competitions contributed for the development of handball trainees, while compared the technical abilities, promoted team actions for the progress of a team as well as, superestimate patient and mutual comprehension. Summing up, the trainees pointed the participation at this competition as an authentic attracted sporting, with positive reflections related to self-esteem and constant effort of training related to future competitions.
Keywords: HandbalL; Competitions; School